The new horizon in 2D electrophoresis: New technology to increase resolution and sensitivity. Issue 11 (5th June 2013) - Moche, Martin; Albrecht, Dirk; Maaß, Sandra; Hecker, Michael; Westermeier, Reiner; Büttner, Knut
Abstract : A principally new type of an electrophoresis setup for the second dimension of 2DE named HPE (high performance electrophoresis) has recently become available that provides excellent reproducibility much superior to traditional 2DE. It takes up ideas from early beginnings of 2DE which could not be satisfactory realized at that time. The new HPE system is in contrast to all other established systems a horizontal electrophoresis that employs a new type of precast polyacrylamide gels on film‐backing and runs on a multilevel flatbed electrophoresis apparatus. In a systematic approach we compared its features to traditional 2DE for the cytosolic proteome of Bacillus subtilis . Not only the reproducibility is enhanced, but also nearly all qualitative parameters as resolution, sensitivity, the number of protein spots (25% more), and the number of different proteins (also additional 25%) are markedly increased. More than 200 proteins were exclusively found in HPE. This new electrophoresis system does not use buffer tanks. No glass plates are needed. Therefore handling of gels is greatly facilitated and very simple to use even for personnel with low technical skills. The new HPE system is technically at the beginnings and further development with increased performance can be expected.